DIRECTIONS OF DEVELOPMENT OF THE PENSION PROVISION SYSTEM OF CITIZENS IN THE REPUBLIC OF UZBEKISTAN - Safaralievich, Mamatov Bahadir (International Journal of Psychosocial Rehabilitation, 2020)
This scientific article is devoted to the study of the pension system of citizens in Uzbekistan. The article studies the stages of evolution of the national pension system, the current state and development trends of pension provision, and identifies problems in the pension system of the republic. Based on the results of the study, scientific proposals and practical recommendations aimed at developing the pension system of citizens of the Republic of Uzbekistan have been developed.